2021
DOI: 10.3390/foods10112743
|View full text |Cite
|
Sign up to set email alerts
|

A Review on High-Power Ultrasound-Assisted Extraction of Olive Oils: Effect on Oil Yield, Quality, Chemical Composition and Consumer Perception

Abstract: The objective of this review is to illustrate the state of the art in high-power ultrasound (HPU) application for olive oil extraction with the most recent studies about the effects of HPU treatment on oil yield, quality, chemical composition, as well as on the consumer’s perception. All the examined works reported an increase in oil yield and extractability index through the use of HPU, which was ascribed to reduced paste viscosity and cavitation-driven cell disruption. Olive oil legal quality was generally n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Although, Nardella et al reported that most of the volatile compounds typical of olive oils are generated during malaxation due to the activation of particular pathways, in which the lipoxygenase (LOX) enzyme plays an essential role in producing a large quantity of C6 aldehydes, esters, and alcohols. These constitute almost all of the positive sensory marks in olive oils [40]. Such changes are initiated when olive tissues are affected, thereby enhancing the liberation of endogenous enzymes like hydroperoxide lyase and lipoxygenase [40].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, Nardella et al reported that most of the volatile compounds typical of olive oils are generated during malaxation due to the activation of particular pathways, in which the lipoxygenase (LOX) enzyme plays an essential role in producing a large quantity of C6 aldehydes, esters, and alcohols. These constitute almost all of the positive sensory marks in olive oils [40]. Such changes are initiated when olive tissues are affected, thereby enhancing the liberation of endogenous enzymes like hydroperoxide lyase and lipoxygenase [40].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…These constitute almost all of the positive sensory marks in olive oils [40]. Such changes are initiated when olive tissues are affected, thereby enhancing the liberation of endogenous enzymes like hydroperoxide lyase and lipoxygenase [40].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Therefore, the urgent development of new techniques for imminent extraction is of utmost importance ( 16 , 17 ). The ultrasound-assisted pretreatment extraction (UAPE) as a pretreatment to HD of ground plant material that is proposed as a substitutable, green, environmentally-friendly, and efficient technique for the separation of plant EO without the addition of any organic solvents ( 18 , 19 ). The promotion of plant EO separation using UAPE is mainly attributed to the generation and explosion of bubbles resulting from water vibration ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several novel and emerging technologies have been developed and applied to satisfy the growing consumer demand for VOO with higher quality and healthrelated composition, such as microwaves [27,28], pulsed electric fields (PEF) [29][30][31][32][33][34][35], and ultrasound treatments [27,[36][37][38][39][40][41][42][43][44][45][46][47]. Moreover, these technologies have been studied for their capability to enhance VOO chemical-sensory quality, as well as its health-related composition.…”
Section: Introductionmentioning
confidence: 99%